Berberine Promotes Cardiac Function by Upregulating PINK1/Parkin-Mediated Mitophagy in Heart Failure - Abudureyimu, Miyesaier; Yu, Wenjun; Cao, Richard Yang; Zhang, Yingmei; Liu, Haibo; Zheng, Hongchao (Frontiers in Physiology, 2020)
Berberine has been verified to protect cardiac function in patients with heart failure (HF). However, the mechanism(s) involved in berberine mediated cardiac protective effects has not been clearly elucidated. The aim of this study was to further investigate the mechanism(s) involved in the beneficial effects of berberine on the transverse aortic contraction (TAC)-induced chronic HF. Mice were randomly divided into four groups. Berberine was administered at a dose of 50 mg/kg/day for 4 weeks via oral gavage. Our findings showed that TAC-induced pressure overload (PO) prompted cardiac dysfunction, cardiac hypertrophy, interstitial fibrosis, cardiomyocyte apoptosis and mitochondrial injury, accompanied with suppressed mitophagy, the effects of which were attenuated by berberine. Furthermore, mitophagy regulators PINK1 and mito-Parkin were downregulated in TAC-induced HF, while berberine upregulated PINK1/mito-Parkin-mediated mitophagy. Notably, knockdown of PINK1 by small interfering RNA significantly suppressed Parkin-mediated mitochondrial ubiquitination and reversed the beneficial actions on HF exerted by berberine. Taken together, our results indicated that berberine plays a critical role in attenuating cardiac hypertrophy and preserving cardiac function from PO induced HF. The potential underlying mechanism is the activation of mitochondrial autophagy via PINK1/Parkin/ubiquitination pathway